Comparative Study of Inheritance Rights In Islam And Civil Law: Analysis of Mashlahah and Maqashid al-Syari`ah - OK. Muhammad al fadli; Syafruddin Syam; Muhammad Syukri Albani Nasution (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2021)
The division of inheritance in the Malay community of Batubara Regency is carried out under prevailing traditional customs. It makes Faraidh law the final (alternative) way after discovering problems during the distribution of inheritance. This article analyzes the review of maslahah and maqashid ash-syari'ah on normal inheritance distribution for the people of Batubara Regency. This research is field research with an empirical study approach. This study found that customary inheritance distribution for the people of Batubara Regency was carried out in various ways, according to the conditions of each inheritance problem. When a wife dies (heir), the inheritance will be directly divided under Islamic inheritance law's provisions; the distribution period is no sooner than 40 days and a maximum of 6 (six) months. If the husband dies (heir), then generally, the inheritance is not distributed until the wife or mother of the heir dies, the heirs of the father or mother are often neglected, and ownership of the house goes to the youngest child or children who live together the heir during life, control of the inheritance is controlled by the eldest son. The customary practice of inheritance distribution for the people of Batubara Regency, which makes the foundation of benefit in the distribution of inheritance in the people of Batubara Regency, is mashlahah mulghah, contrary to the texts of the Koran and the hadiths of the Prophet SAW. In addition, in the maqashid asy-shari'ah scale, it is not achieved regarding the hajiyyat case, namely hifzhul mal